Relationship between grain yield and blossoming in upland rice lines - Fernandes, Monique Carolina Nunes; Castro, Douglas Goulart; Botelho, Flávia Barbosa Silva; Moura, Amanda Mendes de; Tomé, Laís Moretti; Rodrigues, Camila de Souza (Scientia Agraria Paranaensis, 2020)
For upland rice, it is desired, among many objectives, to obtain highly productive and early genotypes, consequently reducing the risk of establishing a crop regarding climatic adversities. Therefore, this study aimed to verify the correlation between the agronomic traits days to flowering and grain yield of 14 upland rice lines. The experiment was conducted in seven environments, in the 2013/14, 2014/15 and 2015/16 crop years, in a randomized complete block design with three replications. Both the genotypic and phenotypic correlation were significant and positive, whereas the genotype correlation was superior to the phenotype. However, it was noted a low magnitude of the correlation values. It was concluded that a favorable and simultaneous selection is possible for high grain yield and plants with early blossoming cycle in upland rice.